2021
DOI: 10.1111/ctr.14528
|View full text |Cite
|
Sign up to set email alerts
|

Organ donor management goals and delayed graft function in adult kidney transplant recipients

Abstract: Background: Delayed graft function (DGF) after kidney transplantation is a common occurrence and correlates with poor graft and patient outcomes. Donor characteristics and care are known to impact DGF. We attempted to show the relationship between achievement of specific donor management goals (DMG) and DGF.Methods: This is a retrospective case-control study using data from 14 046 adult kidney donations after brain death from hospitals in 18 organ procurement organizations (OPOs) which were transplanted to adu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…Kothari et al performed a retrospective case-control study to examine which DMGs are associated with a decreased incidence of DGF. 52 After examining 14 046 cases, they found that meeting DMGs of ≤1 vasopressor (OR .77, 95% CI 0.62-.94; P = .012) and urine output ≥.5 mL/kg/hr (OR .72, 95% CI 0.63-.85; P < .001) were associated with a decreased incidence of DGF. In contrast, meeting a DMG for serum sodium ≤155 mEq/L was associated with an increased incidence of DGF (OR 1.22, 95% CI 1.04-1.42; P = .014).…”
Section: Donor Management Goalsmentioning
confidence: 99%
See 1 more Smart Citation
“…Kothari et al performed a retrospective case-control study to examine which DMGs are associated with a decreased incidence of DGF. 52 After examining 14 046 cases, they found that meeting DMGs of ≤1 vasopressor (OR .77, 95% CI 0.62-.94; P = .012) and urine output ≥.5 mL/kg/hr (OR .72, 95% CI 0.63-.85; P < .001) were associated with a decreased incidence of DGF. In contrast, meeting a DMG for serum sodium ≤155 mEq/L was associated with an increased incidence of DGF (OR 1.22, 95% CI 1.04-1.42; P = .014).…”
Section: Donor Management Goalsmentioning
confidence: 99%
“…In contrast, meeting a DMG for serum sodium ≤155 mEq/L was associated with an increased incidence of DGF (OR 1.22, 95% CI 1.04-1.42; P = .014). 52 More research is needed to help further determine optimal DMG targets, as causal relationships cannot be inferred in retrospective trials.…”
Section: Donor Management Goalsmentioning
confidence: 99%
“…Goal-directed checklists have been found to improve the quality of care and consequently the conversion of brain-dead potential donors to actual organ donors, 8,9,11 the number of organs transplanted per donor, [12][13][14][15] and posttransplant graft function. 16,17 Given the observational nature of these findings and the variability of their protocols for deceased donor care, clinicians and researchers have called for randomized trials to confirm the results. 16,18 The Donation Network to Optimize Organ Recovery Study (DONORS) was a cluster randomized trial designed to evaluate the effectiveness of an evidence-based, goal-directed checklist in the clinical management of brain-dead potential donors in the intensive care unit (ICU).…”
Section: Introductionmentioning
confidence: 99%
“…Goal-directed checklists have been found to improve the quality of care and consequently the conversion of brain-dead potential donors to actual organ donors, the number of organs transplanted per donor, and posttransplant graft function . Given the observational nature of these findings and the variability of their protocols for deceased donor care, clinicians and researchers have called for randomized trials to confirm the results .…”
Section: Introductionmentioning
confidence: 99%
“…Donor management goals, which are standards of care or clinical parameters, have been considered an acceptable barometer of successful donor management[ 9 , 10 ]. Meeting donor management goals has been associated with an increased number of retrieved organs per donor[ 1 , 11 - 13 ] and, more recently, a reduced incidence of delayed graft function[ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%